2011
DOI: 10.1016/j.pnpbp.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Serum BDNF levels before treatment predict SSRI response in depression

Abstract: OBJECTIVES The “neurotrophin hypothesis” of depression posits a role of brain-derived neurotrophic factor (BDNF) in depression, although it is unknown whether BDNF is more involved in the etiology of depression or in the mechanism of action of antidepressants. . It is also unknown whether pre-treatment serum BDNF levels predict antidepressant response. METHODS Thirty un-medicated depressed subjects were treated with escitalopram (N=16) or sertraline (N=14) for eight weeks. Twenty-five of the depressed subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(97 citation statements)
references
References 81 publications
(112 reference statements)
9
83
2
Order By: Relevance
“…The inhibition of serotonin uptake may be substantial in the anti-inflammatory effect of antidepressants [12,40,41]. Moreover, escitalopram can elevate the serum level of BDNF in depressed patients as reported in a previous study [42]. These findings are in agreement with various published data in which escitalopram was individually efficacious in decreasing depression symptoms in comparison with placebo [43,44].…”
Section: Discussionsupporting
confidence: 86%
“…The inhibition of serotonin uptake may be substantial in the anti-inflammatory effect of antidepressants [12,40,41]. Moreover, escitalopram can elevate the serum level of BDNF in depressed patients as reported in a previous study [42]. These findings are in agreement with various published data in which escitalopram was individually efficacious in decreasing depression symptoms in comparison with placebo [43,44].…”
Section: Discussionsupporting
confidence: 86%
“…We have also performed these analyses and observed no significant correlations between changes in MADRS depression score and changes in serum BDNF or VEGF levels. This finding is in agreement with some studies (Ventriglia et al, 2009;Wolkowitz et al, 2011;Yoshimura et al, 2014) and in disagreement with others (Iga et al, 2007;Matrisciano et al, 2009;Minelli et al, 2014).…”
Section: Longitudinal Analysessupporting
confidence: 89%
“…Although not directly comparable, this is in harmony with our previous study (Elfving et al, 2012) showing a significantly higher serum BDNF level in depressed individuals compared to controls and is further supported by a recent metaanalysis showing no significant difference in BDNF concentrations among healthy controls and antidepressant treated depressed patients (Molendijk et al, 2014). Most studies have reported a significant increase in serum BDNF level after antidepressant treatment (Aydemir et al, 2005;Yoshimura et al, 2007Yoshimura et al, , 2014Hellweg et al, 2008;Matrisciano et al, 2009;Wolkowitz et al, 2011;Deuschle et al, 2013), and a few studies have reported a significant decrease (Hellweg et al, 2008;Deuschle et al, 2013). The experimental designs of these studies differ in the type of antidepressant treatment, treatment period, assessment methods, and temperature of serum storage.…”
Section: Longitudinal Analysessupporting
confidence: 85%
“…Moreover, some studies say that changes in BDNF levels are associated with treatment response and only responders show altered levels [13,14] , whereas others found no association between BDNF levels and treatment response [15] . Also, some studies did not consider therapeutic response as a potential factor for BDNF levels regulation [16] .…”
Section: Introductionmentioning
confidence: 99%